Measurement and simulation of myoplasmic calcium transients in mouse slow-twitch muscle fibres - Hollingworth, Stephen (Blackwell Science Inc, 2012)
NON-TECHNICAL SUMMARY: In voluntary muscle cells, the change in the intracellular concentration of calcium ions (ΔµCa(2+)½) controls the contractile cycle by controlling the binding of Ca(2+) to the ‘regulatory’ sites on the troponin molecules attached to the myofilaments. ΔµCa(2+)½ is difficult to measure under physiological conditions, as indicated by the discrepancies in results from recent studies of ΔµCa(2+)½ on mouse slow-twitch muscle fibres. Here we examine some of the reasons underlying these discrepancies and argue that measurements made with membrane-impermeant Ca(2+) indicators that are micro-injected into intact fibres are more accurate than those made with indicators introduced into enzyme-dissociated fibres by diffusion (“AM loading”). Using a computational model, we have analysed the ΔµCa(2+)½ measurements to estimate the kinetic rate constants that govern the reaction of Ca(2+) with the troponin regulatory sites. To our knowledge, this is the first time such estimates have been deduced from physiological measurements in living slow-twitch muscle fibres. ABSTRACT: Bundles of intact fibres from soleus muscles of adult mice were isolated by dissection and one fibre within a bundle was micro-injected with either furaptra or mag-fluo-4, two low-affinity rapidly responding Ca(2+) indicators. Fibres were activated by action potentials to elicit changes in indicator fluorescence (ΔF), a monitor of the myoplasmic free Ca(2+) transient (ΔµCa(2+)½), and changes in fibre tension. All injected fibres appeared to be slow-twitch (type I) fibres as inferred from the time course of their tension responses. The full-duration at half-maximum (FDHM) of ΔF was found to be essentially identical with the two indicators; the mean value was 8.4 ± 0.3 ms (±SEM) at 16°C and 5.1 ± 0.3 ms at 22°C. The value at 22°C is about one-third that reported previously in enzyme-dissociated slow-twitch fibres that had been AM-loaded with mag-fluo-4: 12.4 ± 0.8 ms and 17.2 ± 1.7 ms. We attribute the larger FDHM in enzyme-dissociated fibres either to an alteration of fibre properties due to the enzyme treatment or to some error in the measurement of ΔF associated with AM loading. ΔF in intact fibres was simulated with a multi-compartment reaction-diffusion model that permitted estimation of the amount and time course of Ca(2+) release from the sarcoplasmic reticulum (SR), the binding and diffusion of Ca(2+) in the myoplasm, the re-uptake of Ca(2+) by the SR Ca(2+) pump, and ΔµCa(2+)½ itself. In response to one action potential at 16°C, the following estimates were obtained: 107 μm for the amount of Ca(2+) release; 1.7 ms for the FDHM of the release flux; 7.6 μm and 4.9 ms for the peak and FDHM of spatially averaged ΔµCa(2+)½. With five action potentials at 67 Hz, the estimated amount of Ca(2+) release is 186 μm. Two important unknown model parameters are the on- and off-rate constants of the reaction between Ca(2+) and the regulatory sites on troponin; values of 0.4 × 10(8)m(−1) s(−1) and 26 s(−1), respectively, were found to be consistent with the ΔF measurements.